Avaliação da atividade quelante, antioxidante, anticoagulante, imunomoduladora e cicatrizante do peptídeo aniônico (TanP) da peçonha do escorpião Tityus stigmurus - Melo, Menilla Maria Alves de (2021)
Anionic peptides, or acids, of scorpions correspond to the class of peptides without disulfide bonds, rich in aspartic and / or glutamic acid residues in their primary sequence. TanP is a linear anionic peptide, with 50 amino acid residues and net charge -20, which is present in the venom gland of the scorpion Tityus stigmurus, identified by a transcriptomic approach and after confirmed by mass spectroscopy. A previous study indicated that TanP has a chelating potential for Cu2+ ion, in addition to an immunomodular potential. The therapeutic application of chelating molecules is related to cases of acute or chronic intoxication by metals, neurodegenerative diseases, hematological diseases, healing of skin wounds, cardiovascular diseases and cancer. This work evaluated TanP chelating activity in relation to new metals of biological importance (Fe2+, Ca2+ and Zn2+), by UV-visible spectroscopy, computational methods, and fluorescence, as well as expanding the investigation of the biological potential of the peptide, as an antioxidant, hemostatic, immunomodulatory and wound healing molecule, by in vitro assay. TanP (25 µM) was able to form stable complexes with Fe2+ in a ratio of 1: 5 (TanP: Fe2+). The obtained geometries for Zn2+ and Fe2+ complexes present tetrahedral and octahedral shapes, respectively. Theoretical results suggest that TanP can work as a sensor to identify and quantify Fe2+ ions. The fluorescence intensity of TanP (1.12 µM) decreased significantly after the addition of Fe2+, obtaining that the highest ratio 1: 7.4 (TanP: Fe2+) led to the lowest fluorescence intensity. TanP showed a maximum of 3% of hemolytic activity when evaluated at the highest concentration (50 µM). TanP exhibited DPPH radical scavenging above 70% at all concentrations tested (1 to 25 μM), 89.7% iron chelating activity at 25 μM, 96% hydroxyl radical scavenging activity at 73.6 μM. TanP showed significant anticoagulant activity at concentrations of 12.5 µM and 25 µM for the TP and TTPa assays. No fibrinogenolytic effect was observed. TanP (12.5 and 25 µM) induced release of TNF-α by murine macrophages, in the absence of LPS, this increase being dosedependent. The migration of 3T3 cells was stimulated by TanP (2 µM, 12.5 µM and 50 µM) in an in vitro healing assay. Thus, it is suggesting that the assessment of the chelating potential associated with the antioxidant, anticoagulant, immunomodulatory and healing effects of TanP supports further studies that enable the development of a prototype molecule for therapeutic and biotechnological applications.